Effect Unmanned Aerial Vehicle (UAV) for Topography Mapping at FKAAB - Airul Anuar, Muhammad Azrul Azuwan; Mohamad Abdullah, Nazirah (Recent Trends in Civil Engineering and Built Environment, 2021)
Recently, the user of UAV are increase in application of made topographical mapping. This approach can be the best way for a topographical survey to reduce time and cost. The Ground Sample Distance (GSD) still been questionable, mostly about the precision. These include several fundamental problems, for example, GSD accuracy, UAV output efficiency and UAV output terrain verification. the purpose of this study is to study the effect UAV for topography mapping at “Fakulti Kejuruteraan Awam dan Alam Bina” (FKAAB), UTHM with coordinate (Latitude: 1° 51' 6.59" N, Longitude: 103° 05' 6.60" E) will be obtained from Phantom 4 Pro observations and to evaluate the calculation accuracy of the Ground Sample Distance (GSD) using automated calculation compared to manual calculation methods. Using Phantom 4 Pro to take ortho images from 80 meters, 100 meters and 120 meters above sea level. Pix4D Software and the GSD calculator tool by Pix4D are applied to test the relationship with four altitudes through an automated flight plan. of the study found that automatic and manual calculations differ at distances of 80 meters, 100 meters and 120 meters height increased -0.02 cm / px, -0.03 cm / px and -0.04 cm / px. Thus, altitude adjustment, image overlap, time and production schedule are factors that impede GSD precision. DEM and 3D models received unreliable data due to extensive ortho-maps. Data accuracy loss is due to the higher the height the less the precision of GSD. Due from research, the suitable area of work based on altitude are been provide for surveying work or further research